From microelectrode arrays to all-optical and multimodal neural interfaces: emerging platforms for spatiotemporal interrogation of in vitro neural circuits - Wang, Song; Gordon, Sarah; French, Chris; Unnithan, Ranjith R.; Sun, Dechuan (Frontiers in Synaptic Neuroscience, 2025)
Understanding how synaptic interactions lead to circuit dynamics for neural computation requires experimental tools that can both observe and perturb neuronal activity across spatial and temporal scales. Microelectrode arrays (MEAs) provide scalable access to population spiking activity, yet they lack the spatial resolution and molecular specificity to precisely dissect synaptic mechanisms. In contrast, recent advances in optogenetic actuators, genetically encoded calcium and voltage indicators, and patterned photostimulation have transformed in vitro research, enabling all-optical interrogation of synaptic plasticity, functional connectivity, and emergent network dynamics. Further progress in transparent MEAs and hybrid optical–electrical systems has bridged the divide between electrophysiology and optical control, allowing simultaneous, bidirectional interaction with biological neural networks (BNNs) and real-time feedback modulation of activity patterns. Together, these multimodal in vitro platforms provide unprecedented experimental access to how local interactions shape global network behavior. Beyond technical integration, they establish a foundation for studying biological computation, linking mechanistic understanding of synaptic processes with their computational outcomes. This mini-review summarizes the progression from conventional MEA-based electrophysiology, through all-optical interrogation, to integrated multimodal frameworks that unite the strengths of both modalities.